Randall R. Holmes's Abstract Algebra I PDF

By Randall R. Holmes

Show description

Read or Download Abstract Algebra I PDF

Similar abstract books

K. G. Binmore's Foundations of Analysis: A Straightforward Introduction: PDF

In straightforward introductions to mathematical research, the therapy of the logical and algebraic foundations of the topic is inevitably relatively skeletal. This ebook makes an attempt to flesh out the bones of such remedy by means of delivering a casual yet systematic account of the principles of mathematical research written at an hassle-free point.

Extra info for Abstract Algebra I

Example text

Let σ ∈ Sn . The algorithm illustrated above produces a product σ1 σ2 · · · σm of disjoint cycles. The proof that σ actually equals this product is Exercise 7–6. The proof of the uniqueness statement in the theorem is omitted. In the statement of the theorem the word “product” has a broad meaning including any number of factors, with the case of a product of one factor meaning that element itself. 3 Permutation is product of transpositions Recall that a cycle of length two, like (3, 5), is called a transposition.

We claim that (x−1 1 , x2 ) is an inverse of (x1 , x2 ). We have −1 −1 −1 (x−1 1 , x2 )(x1 , x2 ) = (x1 x1 , x2 x2 ) = (e1 , e2 ) −1 −1 −1 and similarly (x1 , x2 )(x−1 1 , x2 ) = (e1 , e2 ). Therefore, (x1 , x2 ) is an inverse of (x1 , x2 ). This finishes the proof that G1 × G2 is a group under componentwise multiplication. 32 G1 × G2 is the direct product of the groups G1 and G2 . , the binary operations are both +), then the direct product is called the direct sum and it is denoted G1 ⊕ G2 . In this case, the operation is denoted + and it is called componentwise addition: (x1 , x2 ) + (y1 , y2 ) = (x1 + y1 , x2 + y2 ).

Prove that H is a subgroup of G. 2). ) We have e2 = ee = e, so e ∈ H. ) Let x, y ∈ H. We have (xy)2 = xyxy = xxyy (G is abelian) = x2 y 2 (x, y ∈ H) = ee = e. Therefore, xy ∈ H. ) Let x ∈ H. We have x−1 2 = x−2 = x =e (law of exponents) 2 −1 −1 (law of exponents) (x ∈ H) = e. Therefore, x−1 ∈ H. By the Subgroup Theorem, H is a subgroup of G. 3 Cyclic subgroup Let G be a group and let a be a fixed element of G. Put a = {am | m ∈ Z}. 1 Theorem. a is a subgroup of G. Proof. 2). ) We have e = a0 ∈ a .

Download PDF sample

Abstract Algebra I by Randall R. Holmes

by George

Rated 4.84 of 5 – based on 42 votes